Consumer's view on fish consumption in the city of Pirapora - MG (Research, Society and Development, 2022)
As a result of the growing search for healthier eating habits at a more affordable price, the consumption of fish meat has increased in recent years. The city of Pirapora is located in the northern micro-region of the State of Minas Gerais, on the right bank of the Upper Middle São Francisco, where fishing is a traditional activity. With this research, we aim to raise data on the preferences and perceptions of consumers, in the city of Pirapora-MG, on the level of knowledge, regarding the consumption habits and socioeconomic characteristics of consumers. Questions about the knowledge of native, exotic and invasive species were also addressed. With this research, it was possible to draw a diagnosis on the dynamics of consumption and also understand if there is a preference for native species from the São Francisco River, in addition to issues related to the price and access to fish meat, where it was found that the most consumed fish it is the tilapia, even with the presence of the river in the city. However, as shown in the course of the work, in general, more native species are consumed. Thus, as a final outcome, the work helped to better understand the dissemination of information about the importance of native species in the socio-environmental context of communities located on the banks of the São Francisco River.